ISO 9001 certification: customer’s perspective - Matias, Diana (2011)
Based on our own experience and on the literature review carried out the ISO 9001 research studies have mostly addressed certification issues from the companies point of view, namely companies certification motivations and benefits, benefits evolution over time, barriers to the quality management system implementation, evolution and diffusion of worldwide ISO 9001 certification, the impact on organizational and financial performance and the relation between ISO 9001 and Total Quality Management. The ISO 9001 customers’ perspective has not yet been deeply analyzed. This paper reflects a pioneer research project conducted in Portugal with the aim of analyzing the customers’ perspective concerning the product/service quality provides by ISO 9001 certified and non-certified companies. In order to address this issue, a questionnaire was sent to 5100 companies. The response rate was of 7 %.